(untitled) (Nigerian Journal of Technology, 2016)
This work presents the computational modelling of the velocity distribution of an incompressible fluid flowing in a cylindrical annulus pipe, using the finite element method. The result shows that the velocity distribution increases from the boundaries until midway between the boundaries where it was maximum. Also, the velocity increases as the viscosity decreases. The results obtained were compared with exact second order differential equation solution. The results obtained were highly accurate and converges fast to the exact solution as the number of elements increases. http://dx.doi.org/10.4314/njt.v35i2.15